Unexpected outcomes of tislelizumab treatment in thoracic metastasis of malignant phyllodes tumors: a case report and literature review - Liu, Yihao; Duan, Zhixuan; Liu, Minghui; Li, Yongwen; Wang, Min; Chen, Jun; Zhao, Honglin (Frontiers in Oncology, 2025)
Phyllodes tumo (PT) of the breast are classified into benign, borderline, and malignant types. Malignant phyllodes tumor (MPT) with metastasis, particularly those containing sarcomatous components, have a notably poor prognosis. The most common sites of metastasis are the lungs, although metastases can also occur in the pleura and other areas. Metastatic PT is typically treated according to NCCN guidelines for soft tissue sarcomas. The prognosis for patients is extremely poor, with survival typically not exceeding five years. Therefore, the treatment of metastatic MPT presents significant challenges. A 67-year-old female with a history of PT surgery was hospitalized due to acute chest tightness and shortness of breath. MRI revealed a large mass in the left thoracic region, measuring 7.9 × 10.8 × 11.4 cm. A biopsy conducted prior to hospitalization indicated spindle cell soft tissue sarcoma. Due to critical vital signs, she underwent an emergency thoracotomy. Postoperative analysis confirmed the diagnosis of thoracic metastasis from MPT with sarcomatous components. Genetic analysis of the tumor tissue post-surgery revealed a KDM6A gene mutation. Unfortunately, subsequent imaging showed a recurring mass in the left thoracic space, approximately 8 cm in size. Considering the side effects of NCCN-recommended treatments (doxorubicin and ifosfamide) and the high cost of targeted therapies, the patient and her family chose tislelizumab. After six cycles of treatment, the patient’s progression-free survival reached 15 weeks. Due to unsatisfactory treatment effects, the patient and her family decided to discontinue therapy, and the patient passed away in July 2024. Although the combination of surgery and postoperative immune checkpoint inhibitors remains to be validated, this case provides valuable insights into the management of thoracic metastasis from MPT. It offers potential new options for personalized immunotherapy in metastatic MPT.